Group B Streptococcus interactions with human meningeal cells and astrocytes in vitro. - Khalil Alkuwaity; Alexander Taylor; John E Heckels; Kelly S Doran; Myron Christodoulides (PLoS ONE, 2012)
Background Streptococcus agalactiae (Group B Streptococcus, GBS) is a leading cause of life-threatening neonatal meningitis and survivors often suffer permanent neurological damage. How this organism interacts with the meninges and subsequently with astrocytes that constitute the underlying cortical glia limitans superficialis is not known. Methodology/principal findings In this paper, we demonstrate dose-dependent adherence of GBS over time to human meningioma cells and fetal astrocytes in vitro, which was not influenced by expression of either β-haemolysin/cytolysin (β-h/c) toxin, different capsule serotypes or by absence of capsule (p>0.05). Internalization of GBS by both cell types was, however, a slow and an infrequent event (only 0.02-0.4% of associated bacteria were internalised by 9 h). Expression of β-h/c toxin did not play a role in invasion (p>0.05), whereas capsule expression lead to a reduction (p<0.05) in the numbers of intracellular bacteria recovered. GBS strains induced cytotoxicity as demonstrated by the measurement of lactate dehydrogenase (LDH) enzyme release by 9 h and by viable staining. Increasing levels of meningioma cell death correlated with bacterial growth and the phenotype of β-h/c toxin production, i.e. from weakly, to normo- to hyper-haemolytic. However, cytotoxicity was significantly greater (p<0.05) towards astrocytes, and infection with initial MOI≥0.003 induced 70-100% LDH release. By comparing wild-type (β-h/c(+)) and mutant (ΔcylE β-h/c(-)) strains and β-h/c toxin extracts and by using the surfactant dipalmitoylphosphatidylcholine in cytotoxicity inhibition experiments, β-h/c toxin was demonstrated as principally responsible for cell death. Conclusions/significance This study has described key events in the interactions of GBS with meningeal cells and astrocytes in vitro and a major virulence role for β-h/c toxin. Understanding the mechanisms involved will help to identify potential therapies for improving patient survival and for reducing the incidence and severity of neurological sequelae.